2001
DOI: 10.1016/s0008-6363(01)00360-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection with adenosine metabolism inhibitors in ischemic–reperfused mouse heart

Abstract: Adenosine deaminase or kinase inhibition protects from ischemia-reperfusion. Cardioprotection via these enzyme inhibitors requires a functioning purine salvage pathway and involves enhanced adenosine receptor activation. Reduced formation of inosine is unimportant in EHNA-mediated protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 44 publications
9
44
0
Order By: Relevance
“…These data are consistent with and build on previous findings in mouse heart, which demonstrated a role for extracellular Ado and A 1 Ado receptor activation in cardioprotection (Peart et al, 2001). Moreover, this study suggested that cardioprotection may be enhanced by activation of other adenosine receptor subtypes (e.g., A 3 Ado receptors) and that an adenosine salvage pathway was likely to be essential for the full effects of adenosine cardioprotection to be realized.…”
Section: Discussionsupporting
confidence: 92%
“…These data are consistent with and build on previous findings in mouse heart, which demonstrated a role for extracellular Ado and A 1 Ado receptor activation in cardioprotection (Peart et al, 2001). Moreover, this study suggested that cardioprotection may be enhanced by activation of other adenosine receptor subtypes (e.g., A 3 Ado receptors) and that an adenosine salvage pathway was likely to be essential for the full effects of adenosine cardioprotection to be realized.…”
Section: Discussionsupporting
confidence: 92%
“…This corresponds to Ͼ90% inhibition of enzyme activity. Studies in the rat (32) and mouse (227) verify that the majority of adenosine is normally cycled back to 5Ј-AMP and that salvage is markedly inhibited by ischemia. Reduced flux through adenosine kinase has also been reported in deenergized myocytes (295).…”
Section: Generation Of Endogenous Adenosine During Insultmentioning
confidence: 99%
“…Recently, studies employing modulators of adenosine salvage reveal that bypassing phosphorylation enhances ischemic tolerance (226,227). Moreover, protective effects of adenosine are limited by blockade of adenosine kinase, supporting a role for phosphorylation in cardioprotection with adenosine itself (228).…”
Section: Nonreceptor-mediated Cardioprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADENOSINE AND ADENOSINE RECEPTOR agonists have been shown to protect the myocardium from ischemia-reperfusion injury (48)(49)(50). Earlier research focused on the role of the A 1 adenosine receptor (A 1 AR); however, recent evidence suggests that the A 3 adenosine receptor (A 3 AR) may also afford cardioprotection (29,48,50,63).…”
mentioning
confidence: 99%